2008
DOI: 10.1021/jo802207y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Boron-Containing Intermediate in the Boron Tribromide Mediated Aryl Propargyl Ether Cleavage Reaction

Abstract: An alternate reaction mechanism for the boron tribromide mediated deprotection of aryl propargyl ethers based on the isolation of a key boron-containing byproduct is proposed. On the basis of the new mechanistic insight, we discovered that HBBr(2) x SMe(2) can also be used for cleaving aryl propargyl ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…First, we adapted the established bromoboration conditions to our needs (Scheme ). When using simple model alkynes such as 1‐heptyne ( 8a ; Scheme , entry 1) or phenylacetylene ( 8b ; Scheme , entry 2), we found that it was most convenient to follow the procedure described by Yao et al to generate the corresponding boronic acids (i.e., 9 ) 13. These intermediates were not isolated, and instead, condensation with diol 1 14 was carried out directly to give the corresponding boronates (i.e., 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, we adapted the established bromoboration conditions to our needs (Scheme ). When using simple model alkynes such as 1‐heptyne ( 8a ; Scheme , entry 1) or phenylacetylene ( 8b ; Scheme , entry 2), we found that it was most convenient to follow the procedure described by Yao et al to generate the corresponding boronic acids (i.e., 9 ) 13. These intermediates were not isolated, and instead, condensation with diol 1 14 was carried out directly to give the corresponding boronates (i.e., 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Haloboration of alkynes using trihaloboranes is well documented but is restricted to terminal alkynes due to limited electrophilicity at boron [83][84][85]. Calculations on haloboration indicated that increasing electrophilicity at boron results in haloboration becoming more exothermic, and the key transition state barrier also becomes lower in + (26 and 27, Fig.…”
Section: Other Elemento-boration Reactionsmentioning
confidence: 99%
“…Conducting the reaction between PhBCl 2 and 1 a in a variation of solvents ([D 6 ]benzene, [D 8 ]toluene, CH 2 Cl 2 , C 6 H 5 Cl) appeared to make no difference in reactivity with all showing almost quantitative conversion within 9 hours. Additionally, trialling other boron reagents such as BCl 3 as well as the borocation [PhClB(2‐DMAP)][AlCl 4 ] were unsuccessful with a mixture of products prevailing as observed in the resultant multinuclear NMR spectra.…”
Section: Methodsmentioning
confidence: 99%